Case Fatality Rate and Neurological Morbidity in Neonates with Sepsis in a Tertiary Care Neonatal Intensive Care Unit in a Developing Country - Ankit Pachauri; Mala Kumar; Shalini Tripathi; Prachi Singh; S N Singh; Vimala Venkatesh; V K Singh (National Board of Examinations Journal of Medical Sciences)
Background: The case fatality rate (CFR) for neonatal sepsis and its determinants vary from unit to unit. Sepsis may have a detrimental impact on neurodevelopment too. Materials and Methods: It is a descriptive observational study of neonates with culture-proven sepsis to determine the CFR, prevalence, predictors of mortality, and neurological morbidity. A neurological examination (Hammersmith neonatal neurological examination) was done at discharge. Results: The prevalence and CFR of proven sepsis were 24.5% (314/1282) and 24%, respectively. The greatest CFR was seen in neonates with Acinetobacter sepsis. On logistic regression, decreased movements (OR-5.48; 95% CI-2.17–13.83), convulsions at admission (OR-2.42; 95% CI-1.19–4.92), and Acinetobacter in blood culture (OR-1.42; 95% CI-0.65-3.10) were the significant predictors of mortality. Twenty-four (11%) neonates had abnormal neurological examination at discharge and convulsions at admission (OR 3.12; 95% CI 1.04–9.35), and Acinetobacter in blood culture (OR 4.87; 95% CI 1.51–5.66) were the significant predictors of neurological morbidity. Conclusion: A quarter of neonates with sepsis die, and more than a tenth have neurological morbidity.